Tindak Pidana Apostasia (Murtad) Studi Kanonik - Daniel Ortega Galed (Studia Philosophica et Theologica, 2022)
Apostasia, in the penal canon law, is one of the most serious offences. There are at least two fundamental reasons for this; first, apostasia is a direct attack on Christian faith, a fundamental aspect of spiritual life, and secondly, from a juridical perspective, the prescribed canonical sanction is one of the very limited penalties imposed by the codex, namely excommunication latae sententiae (cf. can. 1318). The apostasy is a sensitive and actual topic and therefore needs to be understood properly in order to gain a more comprehensive understanding of it. The concern about the cases of apostasy within the Catholic Church make us learn more about how and when someone really leaves the Catholic faith totally. At the same time, we are invited to understand the various juridical consequences established by canon law for this offence. The ultimate goal of this study is to make a conceptual contribution to the act of apostasia through canonical analysis and to explain how the punishment of excommunication is abolished. The Church through its juridical system judges and at other times also facilitates how the concrete conversions are realized. Keywords: Apostasia, penal canon law, censura, excommunication, the remission of canonical penalties